2017
DOI: 10.1016/j.dyepig.2016.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of novel thieno[3,2- b ]thiophene based metal-free organic dyes with different heteroaromatic donor moieties as sensitizers for dye-sensitized solar cells

Abstract: Four novel heterocycle dyes 3a-d were synthesized in order to study the variations produced in the optical, electronic and photovoltaic properties by substitution of different electron-rich heterocyclic groups to the thieno[3,2-b]thiophene system. The final push-pull conjugated dyes 3a-d were synthesized by Suzuki-Miyaura coupling reaction followed by Knoevenagel condensation of the corresponding aldehyde precursors with cyanoacrylic acid 2a-d. These new push-pull systems are based on a thieno[3,2-b]thiophene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 72 publications
0
28
0
Order By: Relevance
“… b E HOMO = −(4.39 + E ox ) (eV) and E LUMO = −( E red + 4.39) (eV). 59 , 60 c Calculated from the difference between the onset potentials for oxidation and reduction. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… b E HOMO = −(4.39 + E ox ) (eV) and E LUMO = −( E red + 4.39) (eV). 59 , 60 c Calculated from the difference between the onset potentials for oxidation and reduction. …”
Section: Resultsmentioning
confidence: 99%
“…CV was performed using an AUTOLAB electrochemical station in a three-electrode cell configuration, as elsewhere reported, 59 and measured at a scan rate of 0.1 V s –1 (see Figure S13 ). The solutions were deoxygenated by bubbling nitrogen before each measurement.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, recent theoretical and experimental studies showed that proper involvement of thiophene, pyrrole, and furan rings in the chromophore backbone may bring organic materials with advanced properties. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Despite their popularity as auxiliary donors, [32] a combination of five-membered heterocyclic and mesomeric donors has been practically realized only on thiophene. [33][34][35] Pyrrole or furan π-linkers with appended alkoxy or amino mesomeric donors are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…An electrophilic aromatic substitution of the substrate takes place, followed by hydrolysis to yield the heterocyclic carbaldehyde [3]. -Conjugated heterocyclic aldehydes can also be prepared through Suzuki cross coupling reaction using the appropriate coupling components [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%